Growth and fruiting of Ribes magellanicum Poiret in Tierra del Fuego, Argentina - Arena, Miriam Elisabet (2007)
Ribes magellanicum is a Patagonian deciduous shrub, with globose berries, purple at maturity, which can be eaten fresh or used in marmalades and syrups. the aim of this work was to study the shoot growth and fruiting of R. magellanicum in plants growing naturally near Ushuaia city, Tierra del Fuego, Argentina, as a first step towards its later domestication. shoot growth was significantly higher in the northern exposures compared with the southern exposures, as well as in the upper half of the plants in comparison with the lower ones. Fruit production per shoot was significantly higher in 2004 compared with 2003. North‐west and south‐west exposures favored fruit production, whereas the best values were found in the upper half of the plants and in long shoots compared to the lower half of the plants and the short shoots, respectively. R. magellanicum plants growing naturally near ushuaia city, formed c. 900 shoots per plant at the end of the growing season in 2003, whereas nearly 500 fruiting shoots with 595 racemes and 3000 fruits with a weight of 331 g were formed. Sixty‐five percent of the fruiting shoots were in the upper half of the plants. these results are the first antecedents on growth and fruiting of R. magellanicum in Austral Patagonia and are relevant for its later domestication.